Open source tidal turbine: experience of operations at the Marine Energy Test Area (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This was the first tidal energy test carried out at the Marine Energy Test Area (META) in Pembrokeshire, UK. The testing achieved Technology Readiness Level 5 in January 2024. The device is 3 meters in diameter and is positioned below a floating barge. The test site at Warrior Way on the Cleddau river is managed by Marine Energy Wales. The turbine is open source, including technical reports and SolidWorks drawings [1]. It is based on a design concept that has been previously reported [2].Six separate records of velocity were taken, four seabed mounted ADCP units, one ADCP downwards pointing on the barge and an ADV, which was recording at 10Hz and synchronized with the turbine performance data. The primary performance measurement was four pairs of strain gauges measuring blade root bending moments in thrust and torque directions. These were then used to obtain the usual power and thrust co-efficients.Mechanical and operational issues of the deployment are described. Our turbine is designed to operate in remote communities and has a purely mechanical system offshore. The power take off is a water pump and this was a source of issues throughout the test. Test filling of the system revealed that the sliding seal in the front of the turbine had failed since the previous test 12 months earlier. We have also learnt that this system is difficult to align and keep the pump shaft straight through the whole rotation.Overall, a successful test was conducted with several hours of operational results.[1] https://zenodo.org/doi/10.5281/zenodo.8082024[2] https://doi.org/10.1680/jener.21.00101The authors are grateful for funding from the Swansea Bay City Deal and ERDF through the Welsh Government European Funding Office (WEFO).